The Effect of Propolis on Oxidative Damage Induced by Whole Body Irradiation in Rat - Özçelik, Mehtap; Erisir, Mine; Güler, Osman; Baykara, Murat (My University, 2020)
The antioxidant and radioprotective effects of propolis against ionizing radiation induced oxidativedamage were investigated. Twenty one rats were divided in to 3 groups; 1 st group was the controlgroup; 2nd group was the irradiation group, physiological saline (i.p.)/ 3 days + 9 Gy gammairradiation; 3rd group was irradiation + Propolis group, propolis (i.p. 100 mg / kg BW) / 3 days + 9Gy gamma irradiation. As a result of irradiation, a significant increase was determined inmalondialdehyde (MDA) levels of liver, kidney, and brain tissues of the rats (P<0.001). There was asignificant decrease in glutathione peroxidase (GSH-Px) activity of all the tissues (P?0.001) andsuperoxide dismutase (SOD) activity and glutathione (GSH) level in the liver (P?0.01). Also, GSHlevel increased significantly in the kidney (P?0.001) and ovarium tissues (P?0.05). The MDA levelsthat increased in the liver as a result of irradiation, decreased significantly due the addition ofpropolis (P?0.001); whereas, the MDA levels that increased in kidney and brain did not change. Inthe spleen and ovarium tissues, MDA levels decreased significantly as a result of addition ofpropolis compared to the irradiation group (P?0.05). It was determined that GSH levels, thatdecreased in the liver (P?0.01), and increased in the kidney due to addition of propolis, and GSHlevels, that decreased in the liver as a result of irradiation (P?0.01) and increased in the kidney(P?0.001), approached to the normal level (P?0.001) and the GSH levels in the spleen and brainincreased compared to both the control and irradiation groups (P?0.05). The addition of propoliscaused a decrease in the GSH-Px activities of heart, spleen, brain, and ovarium tissues comparedto both the control and irradiation groups (P?0.001). Also, a decrease in the SOD activity of hearttissue compared to the control group was found (P?0.05).
Keywords: Veterinerlik; Biyofizik